Science, engineering and technology in Nigeria. Problems and prospects (2004)
A general overview of the evolution and development of science, engineering and technology in Nigeria has been presented. Five phases of development were Identified between 1960 and 2003. It was observed that while significant efforts have been made at establishing the institution and infrastructure necessary for industrialization, the third important requirement, namely a conducive and political climate has been largely missing. This has led to delay in achieving industrial revolution in the country Other problems affecting science, engineering and technology were identified and some practical solutions have been recommended.